Differential targeting and function of α(2A) and α(2C) adrenergic receptor subtypes in cultured sympathetic neurons - Brum, Patricia C. (2006)
Previous research suggested that α(2A) and α(2C) adrenergic receptor (AR) subtypes have overlapping but unique physiological roles in neuronal signaling; however, the basis for these dissimilarities is not completely known. To better understand the observed functional differences between these autoreceptors, we investigated targeting and signaling of endogenously expressed α(2A) and α(2C)ARs in cultured sympathetic ganglion neurons (SGN). At Days 1 and 4, α(2A) and α(2C)ARs could be readily detected in SGN from wild-type mice. By Day 8, α(2A)ARs were targeted to cell body, as well as axonal and dendritic sites, whereas α(2C)ARs were primarily localized to an intracellular vesicular pool within the cell body and proximal dendritic projections. Expression of synaptic vesicle marker protein SV2 did not differ at Day 8 nor co-localize with either subtype. By Day 16, however, α(2C)ARs had relocated to somatodendritic and axonal sites and, unlike α(2A)ARs, co-localized with SV2 at synaptic contact sites. Consistent with a functional role for α(2)ARs, we also observed that dexmedetomidine stimulation of cultured SGN more efficiently inhibited depolarization-induced calcium entry into older, compared to younger, cultures. These results provide direct evidence of distinct developmental patterns of endogenous α(2A) and α(2C)AR targeting and function in a native cell system and that maturation of SGN in culture leads to alterations in neuronal properties required for proper targeting. More importantly, the co-localization at Day 16 of α(2C)ARs at sites of synaptic contact may partially explain the differential modulation of neurotransmitter release and responsiveness to action potential frequency observed between α(2A) and α(2C)ARs in SGN.